Employment Law in the Digital Age in Regulating Freelance and Remote Workers Through a Comparative Review of Indonesia and Germany - Adinda Intan Cahyani; Ratih Damayanti (Law Research Review Quarterly, 2026)
The reality of employment relationships in Indonesia today far exceeds what is written in labor laws. The emergence of freelance and remote work trends due to digital technology has collided with laws that still rely on formal recognition. The research method used was normative legal research with a regulatory and comparative law approach. The results of the study point to the weak legal protection for freelance and remote workers, including wages, social security, occupational safety and health, and access to dispute resolution mechanisms. In comparison, German law has implemented an adaptive substantive approach. Employment status is assessed based on factual realities and economic dependence, even recognizing the category of quasi-independent workers (arbeitnehmerähnliche Personen) who receive legal protection. Through this comparison, a protection model based on the reality of employment relationships is more relevant to the current shifts in the world of work. On that basis, Indonesia needs to overhaul its labor law policies. By selectively absorbing German legal principles, Indonesia can build a stronger protective barrier for freelance and remote workers amid rapid digitalization.